2014 IEEE 40th Photovoltaic Specialist Conference (PVSC) 2014
DOI: 10.1109/pvsc.2014.6924981
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in the MOVPE technology to increase the process yield and expand the band gap engineering possibilities

Abstract: New approaches to MOVPE material deposition have been developed in order to increase the process yield and expand the band gap engineering possibilities for the realization of high efficiency multijunction (MJ) solar cells. Paradigm changes in the MOVPE growth chamber design have been introduced in order to maintain high thermal homogeneity at the wafer surface also in the case of the growth of strained structures and to allow getting a fast temperature control at the interfaces between arsenide and phosphide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In similar way, III-V compounds have been grown and characterized after SiGeSn growth. It is worth mentioning that a preliminary study of the "cross contamination" was already reported considering the growth of a InGaP/InGaAs/SiGe/Ge TJ structure [18]. This study was limited to measure the contamination of IV elements in III-V after SiGe deposition.…”
Section: Resultsmentioning
confidence: 99%
“…In similar way, III-V compounds have been grown and characterized after SiGeSn growth. It is worth mentioning that a preliminary study of the "cross contamination" was already reported considering the growth of a InGaP/InGaAs/SiGe/Ge TJ structure [18]. This study was limited to measure the contamination of IV elements in III-V after SiGe deposition.…”
Section: Resultsmentioning
confidence: 99%
“…There is considerable interest in exploiting band gap engineering possibilities offered by the integration of III-V and IV-based materials for optoelectronic and more specifically for photovoltaic applications [ 1 , 2 , 3 ]. A successful integration of InGaP and Si has already been accomplished in the realization of dual junction solar cells by mechanical staking the different semiconductors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%